EFFECT OF STRAIN AND TEMPERATURE ON RESPONSE DEGREE OF THE LOCAL IRAQI TURKEY MALES DURING SEMEN ‎COLLECTION - Th. Taha, Nazar; Baha Eldin, S.; Elsardari, S.; W.Eldoori, Tawfiq; J.Hawezy, Dlier (The Iraqi Journal of Veterinary Medicine, 1986)
This study was conducted at the turkey farm of the college of Agriculrure? Salahaddin University, by using (7) black and (10) red local turkey toms to study the effect of strain and environmental temperature on semen volume, time needed for semen collection, frequency of massage and percetage of successful trail, and to study the relation beteen pairs of characters under study.Analysis of variance showed that aenadnie had a significant effect (P<0.05) on both percent of successful trails and the time needed for semen collection, and highly significant (P<0.01) on frequency of massage while it was not significant on the volume of semen.Effect of environmental temperature showed a significant effect (P<0.05) on the percentage of successful trail and highly significant (P<0.01) on other characters.The means of characters showed that the black strain had significantly (P<0.05) exceeded the red strain except for semen volume.Coefficients of correlations between pairs of characters showes a highly significant (P<0.01) relationships they all showed a negative relationships except between time needed for semen collection and percent of successful trails, and between time needed for semen collection and the number of massage, which were positive. While the power of the relationship of all character in the red strain exceeded that of the black one.‎